Pengaruh Suplementasi Rumput Mutiara (Hedyotis corymbosa) dalam Ransum terhadap Penampilan Ayam Broiler - Filawati, Filawati (Fakultas Peternakan Universitas Jambi, 2009)
The present study was conducted to determine the effect of pearl grass (Hedyotis corymbosa) supplementation into the ration on the broiler performance. The study was carried out in the cages under Laboratory of Poultry and Non Ruminant Nutrition and Laboratory of Feed Science, Department ofAnimal Nutrition and Feed Science, Faculty of Animal Science, University of Jambi for 5 months. The study used 2-day of broiler chicken strain MB 202 which fed basal ration. The basal ration contained yellow maize, rice bran, fish meal, soybean meal, Top mix, mineral mix, coconut meal and calciumdiphosphat. The study was assigned by Completely Randomized Design into 5 treatments and 4 replications. The treatments were level of pearl grass supplementation into the ration, namely: M0 (100% basal ration contained 0% pearl grass, as control), M1 (100% basal ration contained 0,2% pearl grass),M2 (100% basal ration contained 0,4% pearl grass), M3 (100% basal ration contained 0,6% pearl grass) and M4 (100% basal ration contained 0,8% pearl grass). Parameters measured were feed intake, daily weight gain, feed conversion ratio, live weight, carcass weight and carcass percentage. Data wereanalyzed by analysis of variance and the significant effects were analyzed by Duncanâ€™s Multiple Range Test (DRMT). Result of this study showed that there was a significantly (P<0,05) decreased on feed intake by pearl grass supplementations. However, pearl grass supplementation had no significantly (P>0,05) affected daily weight gain and feed conversion ratio. It is concluded that pearl grass supplementation into the broiler ration could be implemented up to 0.8% without any affecting on broilerperformance.Â